Essays on Tawhidic epistemology - Spahic, Omer (Dar al-Wahi Publication, 2025)
The themes explored in the book cover a diverse range of issues, including the elements of tawhid in general and tawhidic epistemology in particular as found in the Qur’an and Sunnah; the reciprocal relationship between knowledge and faith, and between worship and epistemology; the importance of studying the Qur’an as the ultimate source of epistemology, as well as the ultimate source of light, truth, and guidance; comparing tawhidic epistemology to the main tenets of its Western counterpart; the decolonization of the Muslim mind and current educational systems in light of tawhidic epistemology; and applying tawhidic epistemology to several crucial sectors of Islamic civilization, such as historiography, philosophy, science, art, and architecture. The objective of this book, which contains twenty-two stimulating essays, is fourfold: to endorse-cum-promote the consequentiality and timeliness of the idea and compelling actuality of Islamic tawhidic epistemology; to discuss several of its critical aspects alongside other key features of Islamic civilization; to apply those aspects to practical dimensions of life; and to draw important parallels between Islamic tawhidic epistemology and that of the West, which is dictated by a different worldview. The essays are written in an engaging manner, inviting critique of the served narratives both in the West and Islamdom, which should be rooted in introspection and critical thinking. This approach aligns with the nature of the tawhidic epistemological framework and represents its first and perhaps most crucial step. Accepting the status quo passively amid widespread ignorance, faithlessness, injustice, and vice would betray the general Islamic tawhidic consciousness and its constant call for affirmative action.